Residual feed intake in Saanen dairy goats: Variability and repeatability from growth to lactation - J.L. Kirkham; F. Zamuner; A.W.N. Cameron; B.J. Leury; A. Carroll; K. DiGiacomo (Journal of Dairy Science, 2025)
ABSTRACT: This experiment investigated the variability and repeatability of residual feed intake (RFI) in growing and lactating dairy goats, aiming to assess its potential as a selection tool for feed efficiency. During the growth phase, 5-mo-old Saanen doelings (n = 60) were grouped based on genetic potential for milk production: high-index (HI; n = 30) and low-index (LI; n = 30) doelings were used. During the lactation phase, 53 early-lactation does, also selected for HI and LI, were used. Of these 53 lactating does, 28 were from the growth phase to investigate the repeatability of RFI rankings. Individual feed intake, ADG, and BCS were recorded during both phases (49 d, plus 7–10 d acclimatization). On 4 occasions, plasma was collected for analysis of metabolic markers. During lactation, milk volume was recorded twice daily, and milk samples were collected twice per week for composition analysis. Goats were classified into high (<−0.5 SD from the mean of RFI), low (>+0.5 SD), and medium (between ± 0.5 SD), and efficiency groups based on RFI for both phases. The RFI variability was greater during lactation (−0.38 to 0.50 kg of DM/d) compared with growth (−0.16 to 0.17 kg of DM/d). During growth, high-efficiency goats consumed 0.18 kg/d less DM for similar production outcomes, with a mean DMI (±SD) of 1.1 ± 0.2 kg/d and an ADG of 226 ± 45 g/d. Lactating goats averaged (mean ± SD) a DMI of 2.6 ± 0.5 kg/d, ECM of 3.4 ± 0.8 kg/d, and an ADG of 139 ± 65 g/d, with high-efficiency goats maintaining reduced feed intake without compromising milk production. No significant correlation between RFI rankings in growth and lactation phases were observed, indicating limited repeatability in RFI ranking across life stages. The variability in RFI across growth and lactation, along with its independence from production traits, highlights its potential as a selection tool for improving feed efficiency in dairy goats. Further investigation into the causes of divergence in RFI and understanding the metabolic and physiological mechanisms is needed to define a more robust trait for selecting more feed-efficient animals.